GetLB: uma nova arquitetura para balanceamento de carga dinâmicos em sistemas de transações eletrônicas financeiras - Andrade, Alexandre Luis de (Universidade do Vale do Rio dos Sinos, 2013)
Electronic financial transactions represents an expanding reality that drives the approach between consumers and suppliers. Transactions can be originated from different information’s capture terminals and are transmitted to a processing center, which decodes, executes and returns the results in the shortest time possible. In particular, this dissertation is framed in the day-to-day operations of GetNet, a network and service provider company, and load balancing on one of its processing systems. The system under study currently has an architecture in which transactions are received at a centralized node, represented by a Cisco switch, and are distributed to machines processors (MP) according to Round Robin scheduling algorithm. This algorithm is suitable for situations where the MP are homogeneous and network transfer time between them and the centralized node is also uniform. This setting can be restrictive for a transactional system that needs to be sized to meet an expanding company and uses geographic MP at different locations. In addition, the performance of Round Robin algorithm enables transactions to be passed to MP who already have high workload or are unavailable. In this context, this work describes an architecture for a transactional system called GetLB, which provides load balancing from the switch based on processing machines’s monitoring. The infrastructure GetLB proposes a new scheduler called LL (Load Level). Unlike the Round Robin, for each transaction i, LL calculates n functions LL (i, j) where j is the target MP and n quantity of machines. This will check their conditions to meet demand as occupancy rate of CPU, memory, disk, and state of the queues of processing machines, among others. The efficient mix of these factors to dispatch transactions, sets the scientific work. As well as the efficiency to notify the switch when asynchronous events occur in the system, such as stopping or loss of processing capacity of some machine. The architecture also aims to provide GetLB operation capability with heterogeneous processing machines, enabling the use of machinery specialists for certain types of transactions and the integration of MPs from different networks (administrative domains). The test results showed that GetLB is more efficient than Round-Robin in many aspects and stand out in case of heterogeneous resources and dynamic events. It was also found that the notifications adds much value to system, assisting in the maintenance and continuous solution’s improvement
Keywords: Sistema de transações eletrônicas financeiras; Balanceamento de carga; Transferência eletrônicas de fundos; Escalonamento dinâmico; Electronic financial transactions system; Electronic funds transfer; Load balance; Dynamic scheduling; ACCNPQ::Ciências Exatas e da Terra::Ciência da Computação